2002
DOI: 10.1103/physrevlett.88.102501
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a New Low-Lying Resonance State inH7e

Abstract: Low-lying resonance states in 7He(6He+n), formed after fragmentation reactions of a 227 MeV/nucleon 8He beam on a carbon target, have been studied. Coincidences between 6He nuclei and neutrons, corresponding to the one-neutron knockout channel in 8He, were selected. The relative energy spectrum in the 6He+n system shows a structure, which is interpreted as the 7He ( Ipi = 3/2(-)) ground state, unbound with 0.43(2) MeV relative to the 6He+n system and a width of Gamma = 0.15(8) MeV overlapping with an excited (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 31 publications
6
34
0
Order By: Relevance
“…Its ground state was identified in the 7 Li(t, 3 He) charge-exchange reaction [1,2] as a J π = 3/2 − resonance with a width of 0.16(3) MeV (full width at half maximum; FWHM) at 0.44(3) MeV above the 6 He +n threshold. This observation was further confirmed by other experiments [3][4][5][6][7][8][9][10], although quantitative values slightly differ, as shown in Fig. 1.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…Its ground state was identified in the 7 Li(t, 3 He) charge-exchange reaction [1,2] as a J π = 3/2 − resonance with a width of 0.16(3) MeV (full width at half maximum; FWHM) at 0.44(3) MeV above the 6 He +n threshold. This observation was further confirmed by other experiments [3][4][5][6][7][8][9][10], although quantitative values slightly differ, as shown in Fig. 1.…”
Section: Introductionsupporting
confidence: 78%
“…Recently, Aksyutina et al [9] carried out an almost identical experiment to that reported in Ref. [4], replacing the carbon target by a liquid-hydrogen target; the low-lying resonance was not confirmed. Furthermore, no evidence for a state below 1 MeV has been found in five other experiments [5,11,12,14,15] using a variety of techniques.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations